Current Knowledge and Computational Techniques for Grapevine Meta-Omics Analysis - Alaimo, Salvatore; Marceca, Gioacchino P.; Giugno, Rosalba; Ferro, Alfredo; Pulvirenti, Alfredo (Frontiers in Plant Science, 2018)
Growing grapevine (Vitis vinifera) is a key contribution to the economy of many countries. Tools provided by genomics and bioinformatics did help researchers in obtaining biological knowledge about the different cultivars. Several genetic markers for common diseases were identified. Recently, the impact of microbiome has been proved to be of fundamental importance both in humans and in plants for its ability to confer protection or induce diseases. In this review we report current knowledge about grapevine microbiome, together with a description of the available computational methodologies for meta-omics analysis.